First aid for the basic sciences general principles - Le, Tao; Krause, Kendall; Takiar, Vinita (McGraw-Hill, 2012)
"The essential companion for your first two years of medical school First Aid for the Basic Sciences: General Principles, 2e provides you with a solid understanding of the basic science principles with which all medical students must be familiar. The second edition has been completely revised to feature a more student-friendly and approachable text, an updated high-yield rapid review section, new images, and more.Delivers comprehensive single-source coverage of the entire first year of medical school Includes important background material most other reviews leave out Covers the high-yield topics and facts tested on the USMLE Offers full-color images, learning aids, tables, and concise text to streamline your study and help you excel in coursework and on the USMLE Provides a framework for understanding anatomy and histology, embryology, behavioral science, biochemistry, microbiology, immunology, pathology, and pharmacology Mirrors the table of content of First Aid for the USMLE Step 1 to facilitate study Written by students who aced the USMLE and reviewed by top faculty "--Provided by publisher.